Introduction: The Contentious Politics of Refugee and Migrant Protest and Solidarity Movements: Remaking Citizenship from the Margins. Issue 5 (3rd July 2016) - Ataç, Ilker; Rygiel, Kim; Stierl, Maurice
Abstract: Throughout the world, political mobilizations by refugees, irregularized migrants, and solidarity activists have emerged, demanding and enacting the right to move and to stay, struggling for citizenship and human rights, and protesting the violence and deadliness of contemporary border regimes. These struggles regularly traverse the local and constitute trans-border, trans-categorical, and in fact, social movements. This special issue inquires into their transformative possibilities and offers a collection of articles that explore political mobilizations in several countries and (border) regions, including Brazil, Mexico, the United States, Austria, Germany, Greece, Turkey and 'the Mediterranean.' This issue brings into dialog social movement literature, and especially the 'contentious politics' perspective, with migration struggles. It connects these to current debates underway within Critical Citizenship Studies and the Autonomy of Migration literatures around rights making, the constitution of political subjectivities, and re-defining notions of the political and political community.